Mitochondrial and nuclear localization of topoisomerase II in the flagellate Bodo saltans (Kinetoplastida), a species with non-catenated kinetoplast DNA - Gaziová, Ivana; Lukes, Julius (The Journal of biological chemistry, 2003)
We have studied topoisomerase II (topo II) in the cells of Bodo saltans, a free-living bodonid (Kinetoplastida). Phylogenetic analysis based on the sequence of the entire topo II gene, which is a single-copy gene, confirmed that B. saltans is a predecessor of parasitic trypanosomatids. Antibodies generated against either an overexpressed unique C-terminal region of topo II or a synthetic oligopeptide derived from the same region did not cross-react with cell lysates of related trypanosomatids, while they recognized a single specific band in the B. saltans lysate. Immunolocalization experiments using both antibodies showed that topo II is evenly dispersed throughout the kinetoplast. This is in striking difference from the localization of topo II in other flagellates, where it occurs in two antipodal centers flanking the kinetoplast disk. Moreover, the same topo II has a distinct localization in multiple loci at the periphery of the nucleus of B. saltans. With a minicircle probe derived from the conserved region we have shown that all relaxed non-catenated minicircles are confined to the globular kinetoplast DNA bundle. Therefore, in the mitochondrion of this primitive eukaryote topo II does not catenate relaxed DNA circles into a network in vivo, while a decatenating activity is present in partially purified cell lysates.
Keywords: Subcellular Fractions; Animals; Base Sequence; DNA-topoisomerasy typu II; sekvenční homologie aminokyselin; Kinetoplastida; Mitochondria; Sequence Homology, Amino Acid; hybridizace in situ; subcelulární frakce; sekvence aminokyselin; Immunohistochemistry; lidé; Cell Nucleus; Molecular Sequence Data; DNA primery; polymerázová řetězová reakce s reverzní transkripcí; Amino Acid Sequence; imunohistochemie; mitochondrie; buněčné jádro; Blotting, Southern; molekulární sekvence - údaje; Reverse Transcriptase Polymerase Chain Reaction; DNA Topoisomerases, Type II; In Situ Hybridization; sekvence nukleotidů; Southernův blotting; DNA Primers; zvířata; Humans